1936
DOI: 10.3382/ps.0150397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minerals and Fiber on Avian Intestinal pH

Abstract: F OR a number of years this station has been conducting a series of experiments with chickens consuming abnormal amounts of minerals either in the mixed feed or in the drinking water. A previous report (Heller, 1933) described the deleterious results produced by the use of excessive amounts of minerals but gave no definite cause of the abnormalities. It has been suggested that the presence of high concentrations of salt might interfere with the normal hydrogenion concentration of the intestinal tract due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
1

Year Published

1942
1942
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
2
6
1
Order By: Relevance
“…Mussehl, Blish, and Ackerson (1935), also using a quinhydrone electrode, showed in an extensive investigation that various diets produced little change in the hydrogen ion concentration of the proventriculus and gizzard and practically no change in the intestine and caecum. These observations were confirmed by Heller and Penquite (1936). Their data showed that while basic salts may raise the pH in the gizzard and crop, the intestine and caeca are unaffected.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Mussehl, Blish, and Ackerson (1935), also using a quinhydrone electrode, showed in an extensive investigation that various diets produced little change in the hydrogen ion concentration of the proventriculus and gizzard and practically no change in the intestine and caecum. These observations were confirmed by Heller and Penquite (1936). Their data showed that while basic salts may raise the pH in the gizzard and crop, the intestine and caeca are unaffected.…”
supporting
confidence: 68%
“…The fact that the birds of other investigators were fed on a diet different from the grain diet used in these experiments could not account for this difference in hydrogen ion concentration in the lower intestine since Penquite and Heller-(1936) as well as Mussehl, Blish, and Ackerson (1935) have shown that the diet exerts little effect on the pH in the lower intestine.…”
Section: Discussionmentioning
confidence: 95%
“…There is in general a correlation between the changes in pH and "free HC1." The data on hydrogen ion concentration agree fairly well with those of Heller and Penquite (1936). The consistently lower pH values obtained in this study are probably due to the fact that the gizzard fluid was removed from live birds.…”
Section: Discussionsupporting
confidence: 84%
“…In these studies the experimental birds were killed and fluid removed from the gizzards for determinations. This same procedure was used by Heller and Penquite (1936) and Mussehl, Blish, and Ackerson (1933) in studying the effect of dietary factors on gastric pH. In the latter investigation the additions of cod liver oil, NaHC0 3 , NH 4 C1, starch, dextrin, sucrose, or lactose were found to affect the gastric pH.…”
mentioning
confidence: 93%
See 1 more Smart Citation